THE CHANGES OF MEANINGS FROM ENGLISH LOANWORDS INTO INDONESIAN - Sultan, Arni Arsyad (Elite : English and Literature Journal, 2025)
Language contact between cultures often leads to the borrowing of words. In addition, arbitrary characteristics of a language may affect to word absorption to another language. Unfortunately, word meaning could be changed from its original meaning and new meaning is created in another language. The research aims to identify the kind of semantic changes which occurred in English loanwords into Indonesian, to disclose the motives of the speakers in using English loanwords, and factors facilitating the semantic changes. The data is the direct utterances gained from daily informal situation among Indonesians located in Makassar, South Sulawesi. It was collected by using fieldwork research observation, questionnaire, and interview. Then, it is analyzed by employing qualitative and descriptive method. The finding reveals that there are six types of semantic changes of English loanwords into Indonesian which are widening or broadening meaning, narrowing meaning, meaning shift, metonymy, metaphor, and synecdoche. The speakers use those English loanwords because of some motives such as the need filling motive and prestige motive. There are also two factors facilitating the speakers in using those English loanwords in their daily life which are social factor and psychological factor.